2021
DOI: 10.3389/fenvs.2021.724483
|View full text |Cite
|
Sign up to set email alerts
|

Regional Non-point Source Pollution Control Method: A Design of Ecological Compensation Standards

Abstract: Reasonable ecological compensation standard is the key to solve farmland non-point source pollution. In the design of compensation standards, the current investigation included ecological benefits in selecting the experimental method. The Multinomial Logit model is used to analyze the willingness of farmers to receive compensation for non-point source pollution control of cultivated land. The results are as follows: 1) Financial compensation can effectively stimulate farmers’ willingness to control non-point s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Among the abiotic effects of runoffs L. Yang et al (18) highlight changes in the hydrological regime of a water object and even channel morphology, as warmer and nutrient-rich runoffs affect the infiltration rate. In addition, this fact is emphasised by the modern scientists H.F. Ehlat Madeco (14) and S. Lu et al (19) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Among the abiotic effects of runoffs L. Yang et al (18) highlight changes in the hydrological regime of a water object and even channel morphology, as warmer and nutrient-rich runoffs affect the infiltration rate. In addition, this fact is emphasised by the modern scientists H.F. Ehlat Madeco (14) and S. Lu et al (19) .…”
Section: Discussionmentioning
confidence: 97%
“…But, therewith, due to the increase in water temperature, the oxygen content in water drops significantly, which destructively affects the fauna of the aquatic environment (15) . Artificial water heating can significantly affect the behaviour of fish, disrupting migration processes and provoking untimely spawning (19) .…”
Section: Consequences Of Wastewater Pollution Of Natural Reservoirsmentioning
confidence: 99%
“…In addition to the effluent from wastewater treatment plants and inflowing rivers, rural domestic pollution sources, agricultural non-point sources, urban runoff, pollutant from residents' living and internal sources within the watershed will also affect the water quality of the reservoir. Studies have shown that the non-point source pollution load can even reach 60%-80% of the total pollution load, which has become the main pollution source of some important water bodies (Zheng et al, 2009;Lu et al, 2021;Hou et al, 2022;Tong et al, 2022). Table 6 shows the inflow and contribution ratios of pollutants such as rural domestic pollution sources, agricultural nonpoint sources, urban runoff, and pollutant from residents' living and internal sources in the Zhangze Reservoir.…”
Section: Water Quality Modelingmentioning
confidence: 99%
“…From the theoretical basis, it has been found that there is an inverted U-shaped relationship between financial technology development and ANSP, so that ANSP can be reduced more effectively by improving the level of financial technology as a main focus (Jiang et al, 2019). At the same time, reasonable ecological compensation standards are also key to solving farmland surface source pollution, and fiscal compensation can effectively stimulate farmers' willingness to control surface source pollution and reduce ANSP (Lu et al, 2021). Based on these, Jiang et al (2020) established a panel-smoothed transformation regression model and concluded that the increase in ANSP due to agricultural economic growth is largely related to the level of financial development and that increasing the level of finance to a medium-high threshold will suppress ANSP (Jiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%